Comparative effectiveness of surgery and radiotherapy for survival of patients with clinically localized prostate cancer: A population-based coarsened exact matching retrospective cohort study - Yasui, Masato (Oncol Lett, 2020)
Radical prostatectomy and radiotherapy are currently the main treatment options for localized prostate cancer. However, no large cohort study comparing surgery and radiation has been performed in Japan or Asia. The objective of the current study was to compare the survival outcomes of patients with clinically localized prostate cancer and in elderly and young patients receiving surgery and radiotherapy. The survival outcomes of patients with localized prostate cancer (age at diagnosis ≤79 years, clinical T1-3) initially treated with surgery or radiotherapy were retrospectively analyzed. Data were collected from the population-based cancer registry of the Kanagawa Prefecture, Japan. A 1:1 coarsened exact matching of age at diagnosis, clinical T stage and cancer differentiation was performed between the two treatment groups. Patients were also categorized into two subgroups by age using a cutoff of 70 years for analysis. The cohort comprised 4,810 patients aged 50–79 years. No significant difference in cancer-specific survival (CSS) was observed between the two groups (P=0.612). However, the surgery group had significantly better overall survival (OS; P=0.004). When stratified for age, similar tendencies were observed in the elderly group (aged 70–79 years; CSS, P=0.961 and OS, P=0.007). No significant difference in either CSS or OS was identified in the younger group (P=0.550 and P=0.408, respectively). Intrinsic deaths were more likely to occur in elderly patients treated with radiotherapy than those undergoing surgery (69.3 vs. 78.2%; P=0.128). The results indicated that surgery provided significantly better OS than radiotherapy, particularly among the elderly. However, no significant difference was observed in CSS. These results should be interpreted with caution, given that some important factors were unavailable in the present study, such as prostate-specific antigen values and Gleason scores. Prospective trials evaluating these therapies are warranted.